Managing object identity with less I/O operations - De Almeida, Fabio Renato [UNESP]; Valencio, Carlos Roberto [UNESP]; Ferrizzi, Andre Cid [UNESP]; Tronco, Mario Luiz; De Souza, Rogeria Cristiane Gratao [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Non-conventional database management systems are used to achieve a better performance when dealing with complex data. One fundamental concept of these systems is object identity (OID). Two techniques can be used for the implementation of OIDs: physical or logical. A logical implementation of OIDs, based on an Indirection Table, is used by NuGeM, a multimedia data manager kernel which is described in this paper. NuGeM Indirection Table allows the relocation of all pages in a database. The proposed strategy modifies the workings of this table so that it is possible to reduce considerably the number of I/O operations during the request and release of pages containing objects and their OIDs. Tests show a reduction of 84% in reading operations and a 67% reduction in writing operations when pages are requested. Although no changes were observed in writing operations during the release of pages, a 100% of reduction in reading operations was obtained. © 2012 IEEE.
Keywords: b+ tree; complex data; direct mapping; hashing; indirect mapping; indirection table; NuGeM; object identifier; object identity; oid; OODBMS